Improving Islamic Religious Education Learning Through the Method of Giving Learning Assignments and Recitations to Grade IV Students of SDN 56, Bengkulu City - Erli Mustika Damayanti (Sekolah Tinggi Ilmu Ekonomi Syariah Nahdlatul Ulama Bengkulu, 2025)
Background: his study aims to determine the increase in student learning achievement after the application of the method of giving learning assignments and recitations, want to know the effect of student learning motivation after the application of the method of giving learning assignments and recitations. Method: the type of research chosen, namely action research, this study uses the action research model from Kemmis and Taggart (in Sugiarti, 1997: 6), which is in the form of a spiral from one cycle to the next. Each cycle includes planning, action, observation, and reflection. Results: From the results of learning activities that have been carried out for three cycles, and based on all the discussions and analyses that have been carried out, it can be concluded as follows: Problem-based learning has a positive impact on improving student learning achievement which is marked by an increase in student learning completeness in each cycle, namely cycle I (68.18%), cycle II (77.27%), cycle III (86.36%). Conclusion: The application of the methods of giving learning assignments and recitations has a positive influence, namely it can increase students' learning motivation as shown by the results of interviews with some students, the average student answer stated that students were interested and interested in the methods of giving learning assignments and recitations so that they became motivated to learn.